KEPERCAYAAN MASYARAKAT TERHADAP PENEGAKAN HUKUM DI INDONESIA - Dr (cand) Andrew Shandy SH.MH Utama (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to explain the public's trust in law enforcement in Indonesia. The method used in this research is normative legal research. Society tends to distrust law enforcement in Indonesia due to the performance of law enforcement officers. Some cases that are striking and attract public attention include the case of Grandma Minah, the BLBI case, the Century Bank case, the Lizard vs Crocodile case, the Akil Mochtar case, the criminalization case of Abraham Samad, and the Setya Novanto case. In fact, the paradigm that is built up in society says that the law is sharp downward and blunt upward. To restore public confidence in law enforcement in Indonesia, one of the strategic steps that must be taken by the government is to clean up law enforcement institutions from corrupt individuals in carrying out their duties and abusing their authority.